Olam Modeling Applications for South Brazil Chuva Experiment Project - Silva, Renato Ramos da; Haas, Reinaldo (Ciência e Natura, 2013)
Neste trabalho apresentamos os resultados obtidos com o modelo OLAM aplicado para alguns eventos ocorridos durante o experimento CHUVA que ocorreu no sul do Brasil nos arredores da cidade de Santa Maria. Os resultados mostraram que o modelo conseguiu simular com bom desempenho a distribuição e acumulação da precipitação ocorrida durante os eventos meteorológicos observados no decorrer do experimento. ABSTRACT: In this study we present the results obtained with the OLAM model applied to a few meteorological events that occurred during the CHUVA Experiment that was carried at the south Brazil near the city of Santa Maria. The results show that OLAM was able to simulate with great performance the distribution and accumulation of precipitation that was recorded during the meteorological events that occurred during the CHUVA field campaign.